Uma arquitetura de suporte a modelagem de simulações de treinamento baseada na arquitetura HLA (High Level Architecture) - Rocha, Rafaela Vilela da (Universidade Federal de São Carlos, 2009)
The use of virtual environments, created by the computer, provides the execution of training simulations in a safe environment to investigate human behaviour and response to dangerous situations. However, building generic virtual environment simulations is a challenge to be researched. At present, existing virtual environment simulations are focused on specific applications. They also have their supporting architecture tightly coupled to the application making extensions or modifications difficult and dependent on computing specialists. Thus, it is important that environments that ease the building of these simulations be created. This work aims to specify an architecture to support the development, implementation, management, control and analysis of collaborative virtual environments, in conformance with the High Level Architecture, a reference architecture for simulations interoperability and reuse. In this work, simulation construction is driven by non-linear, interactive storytelling and instantiated ontologies. The history and ontologies integration facilitates the creation of different simulations without the need for programmers. The goal of the collaborative virtual environment simulations to be created is training for emergency preparedness and response application domain. However, new application domains can be designed by integrating new ontologies. For the ontologies creation, norms for protection against fire and exercise protocols, in use at São Paulo State, were used along with expert advice by São Carlos fire fighters. An environment for the creation of simulations is being developed as part of this work, as well as the whole process of development and execution of a simulation using our proposed architecture. A use case (fire and explosion occurrence) was devised for simulation instantiation. As the main results of this work a novel architecture was devised for the creation of complex training simulations as well as seven ontologies in the emergency management domain. These can be used as powerful tools for the creation of training simulations for the emergency preparedness and response teams.
Keywords: Ambiente virtual; Simulação por computador; Ontologia; História interativa não linear; Ontologia; Simulation; Collaborative virtual environments; High Level Architecture; Ontology; Non-linear interactive storytelling; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO